"The Aten desires that there be made for him": An analysis of Amenhotep IV/Akhenaten's Temple Construction Activity outside of Tell el-Amarna - Paqua, Megan Kathryn (AUC Knowledge Fountain, 2015)
The Amarna Period is one of the most widely studied periods of ancient Egyptian history, largely due to the wide variety of cultural material available from the eponymous settlement Tell el-Amarna, the ancient city of Akhetaten. However, there is a great deal of archaeological and textual evidence for during the Amarna Period activity outside of the city of Akhetaten. This thesis investigates the regional temples constructed by Amenhotep IV/Akhenaten throughout the course of his reign. It establishes a set of criteria to evaluate the archaeological and textual evidence for temple construction at different sites across Egypt in order to determine which structures constitute an Amarna Period construction as opposed to later reuse of Amarna Period materials taken from other sites. The thesis examines the regional temples first as a discrete group, to examine the geographic scope of Amarna Period temple activity, and then places the regional sites in comparison with the temples from Tell el-Amarna to assess the evolution of the architectural layout and iconographic program, thus elucidating the trajectory of the corresponding changes made to state theology throughout the Amarna Period. These transformations represent not only a religious revolution, in which the orthodoxy of New Kingdom state religion is supplanted, but also the acceleration of the pre-existing New Kingdom trend towards the solarization of state cults as well as the centrality of the person of the king in his role as the main officiant of cult.